Application SEM-EDX in Biodegradation of Seafood Wastes by Sponge-Derived Actinomycetes 19C38A1 in Solid Fermentation. Issue 1 (December 2021) - Widyastuti,; Hendri, J; Setiawan, A
Abstract: Biodegradation of chitin by microorganisms can produce derivative products that have economic value. This research aims to apply SEM-EDX analysis in observing the biodegradation process of seafood industrial waste by actinomycetes. Shrimp shells, cuttlefish bones and fish scales were obtained from the free market. In the early stages, the SEM-EDX spectrum analysis of the substrate showed almost the same carbon, oxygen, and mineral compositions. While the surface of each substrate is quite varied. On the second day of the fermentation, SEM image analysis showed that the growth rate of actinomycetes on each substrate was significantly different. The difference in growth was supported by SEM imaging data which showed damage to the surface of each substrate. Further analysis of the degradation products by HPLC on the second and third days showed the formation of glucosamine. It suspected that actinomycetes can break down shrimp shell waste into glucosamine. This information is very important as the basis for further research related to the optimization of the glucosamine and chitooligosaccharide (COS) production process using the solid fermentation method.